Cryopreservation of bioflavonoid-rich plant sources and bioflavonoid-microcapsules: emerging technologies for preserving bioactivity and enhancing nutraceutical applications - Xiang, Jia; Mlambo, Ronald; Shaw, Ibrahim; Seid, Yimer; Shah, Hamid; He, Yongju; Kpegah, Julius K. S. K.; Tan, Songwen; Zhou, Wenhu; He, Binsheng (Frontiers in Nutrition, 2023)
Bioflavonoids are natural polyphenolic secondary metabolites that are medicinal. These compounds possess antitumor, cardioprotective, anti-inflammatory, antimicrobial, antiviral, and anti-psoriasis properties to mention a few. Plant species that contain bioflavonoids should be preserved as such. Also, the bioactivity of the bioflavonoids as neutraceutical compounds is compromised following extraction due to their sensitivity to environmental factors like light, pH, and temperature. In other words, the bioflavonoids' shelf-life is affected. Scientists noticed that bioflavonoids have low solubility properties, poor absorption, and low bioavailability following consumption. Researchers came up with methods to encapsulate bioflavonoids in order to circumvent the challenges above and also to mask the unpleasant order these chemicals may have. Besides, scientists cryopreserve plant species that contain bioflavonoids. In this review, we discuss cryopreservation and bioflavonoid microencapsulation focusing mainly on vitrification, slow freezing, and freeze-drying microencapsulation techniques. In addition, we highlight bioflavonoid extraction techniques, medicinal properties, challenges, and future perspectives of cryopreservation and microencapsulation of bioflavonoids. Regardless of the uniqueness of cryopreservation and microencapsulation as methods to preserve bioflavonoid sources and bioflavonoids' bioactivity, there are challenges reported. Freeze-drying technology is costly. Cryoprotectants damage the integrity of plant cells, to say the least. Researchers are working very hard to overcome these challenges. Encapsulating bioflavonoids via coaxial electrospray and then cryopreserving the micro/nanocapsules produced can be very interesting.